Testing gustatory function using either a forced-choice or a non-forced-choice paradigm - Does it make a difference? - Besser, G.; Prassl, A.; Mueller, C. A.; Renner, Bertold (Rhinology, 2019)
BACKGROUND: Recently more interest is evolving for research on gustatory function, also due to findings of “extraoral” taste receptors with postulated participation in a pathogen detection network. Also, bitter taste function seems to be reduced in patients with chronic rhinosinusitis. For testing gustatory function “taste strips” (TS) have been validated in a forced-choice (fc) and a non-forced-choice (nfc) paradigm and used in several studies. Purpose of the investigation was to evaluate possible differences of named modalities. METHODOLOGY: Healthy subjects (n=102) with subjective normal gustatory function and patients (n=30) with potential taste dysfunction were included. All participants were tested twice (using TS in four concentrations of sweet, sour, salty, and bitter taste), either starting with a fc or a nfc paradigm. RESULTS: In tested patients there was a difference between fc and nfc procedure with higher results for bitter in the fc testing procedure, while other qualities did not differ. This effect was also visible in the overall participants with higher scores in the fc procedure for bitter taste. CONCLUSION: TS are valid to be used in a forced and a non-forced choice paradigm, with bitter taste showing slightly higher scores in forced-choice testing. Future investigators with focus on bitter taste perception should be particularly cautious when comparing results in regard to testing procedure.
CRIS-Team Scopus Importer:2019-10-11